Pengembangan Bahan Ajar Modul Scrapbook Pada Pembelajaran Tematik Terpadu - Octavianty, Alma Rizkya Krismonika Nurfajri; Djuanda, Dadan; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2021)
The purpose of this study was to describe the description of distance learning activities, to know the design of scrapbook module teaching materials in integrated thematic learning and to know the expert validation of scrapbook module teaching materials in integrated thematic learning. This research was conducted because of the lack of creative and fun learning. The instruments used are interview guidelines, field notes format, validation sheets, lesson plans. Initial data collection techniques used interviews, observations and field notes. The research method used is descriptive research method, Model Design and Development or research and development with a qualitative approach. The results showed that the validation of the development of scrapbook module teaching materials by material experts, media experts and users showed that scrapbook module teaching materials in integrated thematic learning were categorized as very feasible to use based on the conversion of assessment criteria.